Density and Abundance of Prey Species in Ranthambhore Tiger Reserve - Gurjar, Raju Lal; Chhangani, Anil Kumar (Indian Forester, 2019)
The density and abundance of prey species have been estimated in Ranthambhore Tiger Reserve. Authors estimated 128.44 animals of all prey, 05.83 animals of wild prey and 117.24 animals of livestock per km2 in Ranthambhore National Park and 92.39 animals of all prey, 03.16 animals of wild prey and 89.70 animals of livestock per km2 in human landscape area. All prey, wild prey and livestock are more in Ranthambhore National Park than human landscape. Tigers are dispersed from Ranthambhore National Park to human landscape area and survive on livestock base in human landscape because of wild prey is very less in human landscape areas compared to Ranthambhore National Park.